Stress in Dentistry - Marlin Jena; Dharmashree Satyarup; Ramesh Nagarajappa; Upasana Dhar (Current Overview on Disease and Health Vol. 7, 2023)
Dentists are prone to have different kinds of mental, physical, psychological and financial issues that could cause stress. Numerous studies have found that dentistry students experience higher stress than students in any other profession. It is crucial for dentists to de-stress by minimising the stress and improving their capacity to handle stressful circumstances. So that stress can be decreased to a manageable level, behaviours like resisting stress as well as time management and selecting goals that are analogous to real-life scenarios should be promoted. As in any profession, transition from academics to workplace could be a challenging task, as dental professionals have responsibility for the health status of people. Therefore, it is essential that stress management and reduction programmes, which can offer real solutions for reducing various types of stress, be incorporated into dental education. This review focuses on how to promote and enhance the well-being of the dentists by reduction of stress related to their profession.